Bats, Fever and Adenopathy – What Is the Link? - Joshua J Manolakos; Mohan Cooray; Ameen Patel; Shariq Haider (Canadian Journal of Infectious Diseases and Medical Microbiology)
A case of travel-related, subacute, progressive disseminated histoplasmosis in a nonimmunocompromised individual is described. The present case highlights the environmental exposure to Histoplasma capsulatum in Costa Rica, the diagnostic approach and treatment options, as well as new alternatives for salvage therapy for histoplasmosis infection.